Multimodal CT versus MRI in Selecting Acute Stroke Patients for Endovascular Treatment - García-Bermejo, Pablo (S. Karger AG, 2013)
Arterial revascularization is the most effective therapy for acute stroke patients. Systemic thrombolysis with recombinant tissue plasminogen activator based on baseline non-contrast CT (NCCT) imaging criteria is the only treatment approved to date, which is limited by severe timing and medical restrictions, and a narrow efficacy. The simple imaging methodology required contrast with the current wide range of imaging modalities available, which permits the physician to rapidly obtain an estimation of the most relevant pathophysiological factors involved in an acute stroke, overcoming the limited capability of NCCT. Multimodal CT and MRI combine techniques that aim to depict the neurovasculature and the status of the brain parenchyma, including the presence of hemorrhage and infarction, as well as the viability of the cerebral ischemic areas involved. These additional imaging procedures have been explored in clinical studies and trials to guide intravenous thrombolysis in acute stroke patients beyond the currently established time windows, with inconclusive results. However, emergent endovascular materials and techniques are evolving, showing promising results with increasing rates of arterial recanalization with an acceptable safety profile, therefore becoming a potential alternative and complimentary treatment, although the current lack of a high level of evidence is limiting their use in routine clinical practice. Nevertheless, these advanced neuroimaging methods can be used to improve the selection of candidates for these novel invasive therapies and, moreover, to help the interventionist to design a faster and safer procedure. In this article, we review the basic aspects of both CT and MRI modalities and the state of the evidence of these imaging tools to guide endovascular therapy, as well as the advantages and disadvantages of each method.